4x = -60 - 19y
-7x = -48 - 19y
Subtract the bottom equation from the top:
4x + 7x = -60 + 48 - 19y + 19y
Simplify:
11x = -12 -0y
11x = -12
Divide both sides by 11:
11x/11 = -12/11
Simplify:
x = -12/11
Then plug in x to solve for y:
4(-12/11) = -60 - 19y
Simplify:
-48/11 = -60 - 19y
Add 60 to both sides (keep in mind 60 = 660/11):
-48/11 + 660/11 = -60 + 60 - 19y
Simplify:
612/11 = 0 - 19y
612/11 = -19y
Divide both sides by -19 (keep in mind that dividing by -19 is the same as multiplying by -1/19):
612/11 • -1/19 = -19y/-19
Simplify:
-612/209 = y
y = -612/209
So, the answer is: (-12/11, -612/209)